ToF-SIMS spectral analysis of pristine and neutron irradiated single crystal tungsten - Parker, Gabriel D.; Misicko, Tobias K.; Teriler, Tanguy; Xiao, Yang; Yu, Xiao-Ying (Results in surfaces and interfaces, 2025)
Time-of-flight secondary ion mass spectrometry (ToF-SIMS) has many promising features in studying materials including high spatial resolution and high mass accuracy of elements, molecules, and isotopes. Its ability to resolve isotopes is especially attractive in studying transmutation products of single crystal tungsten (SCW) post neutron irradiation. Tungsten (W) is a contender of plasma facing materials (PFMs) due to its high thermal and radiological stability. PFMs to be used in the construction of fusion vessels are subject to high temperature and neutron irradiation, resulting in changes to materials including transmutation, which ultimately impact material mechanical and thermal properties. We used IONTOF TOF.SIMS V instrument equipped with a 30 keV Bi3+ primary ion beam to study pristine SCW and irradiated SCW speciemens. Scanning electron microscope coupled with focused ion beam (SEM-FIB) was used to reduce the dosage of neutron irradiated tungsten and prepare for specimens for SIMS analysis. Static ToF-SIMS spectra were obtained, and transmutation product peak identification was presented in this work. Identified molecules and molecular fragments were compared against isotope theoretical mass to charge ratios of tungsten, rhenium, osmium, and other relevant products. Our results show that ToF-SIMS provides a viable means to study transmutation products of W post neutron irradiation. Such applications are suitable to investigate transmutation effects on materials that are being considered and developed for fusion pilot plants. [Display omitted] •ToF-SIMS offers sensitive and selective isotopic analysis of tungsten.•Provide high mass resolution spectra of single crystal tungsten and isotopes.•Provide ToF-SIMS spectral reference data of neutron irradiated tungsten.•Analysis of transmutation products performed using ToF-SIMS.•Reveal tungsten transmuted products from depth profiling free of contamination.